Management, vaccination status and COVID-19 morbidity of patients with Gaucher disease in Germany during the COVID-19 pandemic - Niederau, Claus; Regenbogen, Claudia; Fruehauf, Hans-Martin; Merkel, Martin; Ziagaki, Athanasia; Mengel, Eugen; Baerwald, Christoph; Muschol, Nicole; Staufner, Christian; Lampe, Christina; Gillessen, Anton; Koehler, Jan Philipp; vom Dahl, Stephan (Zeitschrift für Gastroenterologie, 2023)
Background Continuation of standard management of Gaucher disease (GD) has been challenging during the COVID-19 pandemic, resulting in infrequent/missed infusions and follow-up appointments. Little data are available on the consequences of these changes and on the SARS-CoV-2 vaccinations in German GD patients.Methods A survey with 22 questions about GD management during the pandemic was sent to 19 German Gaucher centres. It was answered by 11/19 centres caring for 257 GD patients (almost ¾ of the German GD population); 245 patients had type 1 and 12 had type 3 GD; 240 were ≥ 18 years old.Results Monitoring intervals were prolonged in 8/11 centres from a median of 9 to 12 months. Enzyme replacement therapy (ERT) was changed to home ERT in 4 patients and substituted by oral substrate reduction therapy (SRT) in 6 patients. From March 2020 to October 2021, no serious complications of GD were documented. Only 4 SARS-CoV-2 infections were reported (1.6%). Two infections were asymptomatic and two mild; all occurred in adult type 1, non-splenectomized patients on ERT. Vaccination rate in adult GD was 79.5% (95.3% mRNA vaccines). Serious vaccination complications were not reported.Conclusions The COVID-19 pandemic has lowered the threshold for switching from practice- or hospital-based ERT to home therapy or to SRT. No major GD complication was documented during the pandemic. Infection rate with SARS-CoV-2 in GD may rather be lower than expected, and its severity is mild. Vaccination rates are high in GD patients and vaccination was well tolerated.
Keywords: Morbus Gaucher; COVID-19; Angeborene Stoffwechselstörung